2019
DOI: 10.1101/854703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reorienting Spatial Attention within Visual Working Memory

Abstract: 4Attention and working memory (WM) are intertwined core cognitive processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 91 publications
(151 reference statements)
1
2
0
Order By: Relevance
“…We simultaneously measured neural activities with magnetoencephalography (MEG) in this experiment. Relevant findings can be found in another paper (Han & Ku, 2019).…”
Section: Stimuli and Apparatussupporting
confidence: 68%
See 2 more Smart Citations
“…We simultaneously measured neural activities with magnetoencephalography (MEG) in this experiment. Relevant findings can be found in another paper (Han & Ku, 2019).…”
Section: Stimuli and Apparatussupporting
confidence: 68%
“…But how could this happen? Our previous work (Han & Ku, 2019) suggested that the stronger prefrontal activities of peripheral retro-cues relative to central retro-cues, the larger behavioral differentiations between the two types of retro-cues. Given that the activations in prefrontal regions have been reported to play a causal role in confidence ratings (Kwok, Cai, & Buckley, 2019), we proposed one possible account that confidence ratings in this experiment may make the prefrontal activities in the central retro-cue task more alike to the peripheral one, and thus led to no difference between the two retro-cues.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation